Parenting Style for Single Mothers in Yogyakarta - Indah Andika Octavia (Universitas Islam Negeri Imam Bonjol Padang, 2022)
A single mother is not an option in a woman’s life. When you become a single mother, there will be changes in the family, including changes in the roles and duties that single mothers in raising children must bear. Including how to apply rules, teach values and norms, give attention and affection, and show good attitudes and behavior to become examples or role models for their children. Therefore, research related to how the dynamics of a single mother apply the parenting style that she gives to her children is fascinating to study. The subject of this research is a single mother who has one child. The study results found two themes, namely the role of parents and knowledge about parenting. In addition, there are also several impacts of inconsistent parenting related to children’s behavior. Children tend to be temperamental, irritable, and have weak emotional control.